Isolated v-lesion represents a benign phenotype of vascular rejection of the kidney allograft - a retrospective study - Novotny, Marek; Hruba, Petra; Vichova, Petra; Maluskova, Jana; Honsova, Eva; Viklicky, Ondrej; Wohlfahrtova, Mariana (Transplant international, 2018)
While the detrimental impact of the humoral acute vascular rejection (AVR) phenotype is recognized, the prognostic significance of isolated v-lesion (IV) remains unclear. In this retrospective single-centre study, AVR was found in 98 of 1015 patients (9.7%) who had undergone kidney transplantation in 2010-2014, with donor-specific antibodies (DSA) evaluated in all of them. The outcome of four AVR phenotypes was evaluated during median follow-up of 59 months; in 25 patients with IV, 18 with T-cell-mediated vascular rejection (TCMVR), 19 with antibody-mediated vascular rejection (AMVR) and 36 with suspected antibody-mediated rejection (sAMVR). AVR was diagnosed mainly by for-cause biopsy (81%) early after transplantation (median 19 POD) and appeared as mild-grade intimal arteritis. IV occurred in low-sensitized patients after the first transplantation (96%) in the absence of DSA. IV responded satisfactorily to treatment (88%), showed no persistence of rejection in surveillance biopsy, and had stable graft function, minimal proteinuria and excellent DCGS (96%). Contrary to that, Kaplan-Meier estimate of 3-year DCGS of AMVR was 66% (log-rank = 0.0004). Early IV represents a benign phenotype of AVR with a favourable outcome. This study prompts further research to evaluate the nature of IV before considering any change in the classification and management.
Keywords: renální insuficience; dospělí; Kidney; rejekce štěpu; Kaplan-Meier Estimate; Female; Graft Rejection; Phenotype; Adult; ženské pohlaví; Kaplanův-Meierův odhad; biopsie; Time Factors; časové faktory; lidé; Immunosuppressive Agents; Antibodies; T-lymfocyty; transplantace ledvin; Middle Aged; retrospektivní studie; Kidney Transplantation; Male; Biopsy; riziko; Graft Survival; HLA antigeny; lidé středního věku; fenotyp; mužské pohlaví; Risk; T-Lymphocytes; Renal Insufficiency; ledviny; HLA Antigens; Retrospective Studies; přežívání štěpu; protilátky; imunosupresiva; Humans